Implementation of The Guided Inquiry Learning Model With Chemmind Map to Improve Chemistry Learning Activities And Achievements In The Topic Redox Reaction - Maya Firda Hidayah; Suryadi Budi Utomo; Sri Yamtinah (Universitas Sebelas Maret, 2021)
This study aims to increase student learning activities and achievement on redox reactions subject matter in class X IPA 2 SMA Negeri 1 Ngemplak Boyolali through the implementation of a guided inquiry learning model with chemmind map media. This study applies the Classroom Action Research procedure according to Kemmis and Mc Taggart in two cycles. Each cycle consists of planning, implementation, observation, and reflection. The research subjects were students of class X IPA 2 SMA Negeri 1 Ngemplak Boyolali in the 2016/2017 academic year as many as 37 students. The object of research is student learning activities and achievements. Activities include visual activities, oral activities, listening activities, and writing activities. Sources of data come from teachers and students. Data collection techniques through observation, interviews, tests, questionnaires, and documentation studies, then analyzed using qualitative and quantitative methods. The validity of the data using the method triangulation during the learning process from home and the use of technology as an alternative solution to these challenges. technique. The results showed an increase in student activity and achievement. The percentage of achievement of student learning activities during the first cycle was 97.30%. The learning achievement in the knowledge aspect in the first cycle was 54.05% increased to 86.49% in the second cycle, the attitude aspect was 97.30% in the first cycle, and the skills aspect was 100% in the first cycle. With the guidance of the teacher, students have able to compile the chemmind map media according to Buzan's theory with 100% achievement in cycle I.